The Relationship Between Democratic Teaching Style and Learning Motivation of Grade Ivb Students of Sdn Karangrejo Ii - Imroatus Solihah; Tri Linggo Wati (Syntax Corporation Indonesia, 2023)
This study aims to examine whether there is a relationship between the democratic teaching style and student learning motivation. Respondents seen in this study amounted to 40 elementary school students. The method used is a quantitative method using the correlation coefficient of Spearman with the help of IBM SPSS version 23 for windows. The measuring instrument used was the democracy teacher's teaching style questionnaire totaling 20 items and the student learning motivation questionnaire totaling 35 items. From the hypothesis testing in this study, it shows that the significance value is 0.05 <0.33, thus the hypothesis proposed by the researcher is accepted, meaning that there is a large relationship between the democratic teaching style and the learning motivation of class IVB students at SDN Karangrejo II